2016
DOI: 10.1371/journal.pone.0167000
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Red Blood Cell Distribution Width in Non-Cardiovascular Critically or Acutely Patients: A Systematic Review

Abstract: BackgroundRDW (red cell distribution width) has been reported to been associated with the prognosis of patients with cardiovascular diseases. However, RDW is often overlooked by clinicians in treating patients with non-cardiovascular diseases, especially in an emergency. The objective of this systematic review is to explore the prognostic value of RDW in non-cardiovascular emergencies.MethodsPubMed, EMBASE, and the Cochrane Central Register of Controlled Trials were systematically searched from their inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 56 publications
3
40
1
Order By: Relevance
“…RDW showed no baseline difference in HF patients with different severities (Table ) and no in‐hospital variation in the selected patients with acutely decompensated HF. Worse primary outcome was found in older adults showing RDW ≥15% in both HF (Table ) and infection (Table ), as in the literature, indicating that RDW is a simple, stable and sensitive prognostic factor in these common diseases . As senile HF and infection are fatal, these findings are important in gerontology.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…RDW showed no baseline difference in HF patients with different severities (Table ) and no in‐hospital variation in the selected patients with acutely decompensated HF. Worse primary outcome was found in older adults showing RDW ≥15% in both HF (Table ) and infection (Table ), as in the literature, indicating that RDW is a simple, stable and sensitive prognostic factor in these common diseases . As senile HF and infection are fatal, these findings are important in gerontology.…”
Section: Discussionsupporting
confidence: 67%
“…A large‐scale cohort is standard to study the association of RDW with HF . Second, HF management protocol and antibiotic treatment strategy depend on the discretions of the treating physicians, although the discretions were strictly based on the guidelines of the domestic medical societies . Third, this observational study did not contain a healthy control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have indicated that patients with higher RDW levels were associated with an increased risk of cardiovascular (CV) events and new-onset stroke [ 3 5 ]. Moreover, the level of RDW was positively correlated with mortality in patients with acute or critical illnesses, in those with chronic diseases, and in healthy cohorts [ 6 13 ]. Patel et al reported a 14% increased risk of death for each 1% increment in RDW in a community-based elderly population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%